Tuning of Redox Regulatory Mechanisms, Reactive Oxygen Species and Redox Homeostasis under Salinity Stress - Hossain, M. Sazzad; Dietz, Karl-Josef (Frontiers in Plant Science, 2016)
Soil salinity is a crucial environmental constraint which limits biomass production at many sites on a global scale. Saline growth conditions cause osmotic and ionic imbalances, oxidative stress and perturb metabolism, e.g. the photosynthetic electron flow. The plant ability to tolerate salinity is determined by multiple biochemical and physiological mechanisms protecting cell functions, in particular by regulating proper water relations and maintaining ion homeostasis. Redox homeostasis is a fundamental cell property. Its regulation includes control of reactive oxygen species (ROS) generation, sensing deviation from and readjustment of the cellular redox state. All these redox related functions have been recognized as decisive factors in salinity acclimation and adaptation. This review focuses on the core response of plants to overcome the challenges of salinity stress through regulation of ROS generation and detoxification systems and to maintain redox homeostasis. Emphasis is given to the role of NADH oxidase (RBOH), alternative oxidase (AOX), the plastid terminal oxidase (PTOX) and the malate valve with the malate dehydrogenase isoforms under salt stress. Overwhelming evidence assigns an essential auxiliary function of ROS and redox homeostasis to salinity acclimation of plants.